THE EFFECT OF PRODUCT QUALITY AND PRICE ON CUSTOMER REPURCHASE INTEREST OF SAMSUNG SMARTPHONE WITH SATISFACTION AS MEDIATION VARIABLE - Fadhilrahmansyah Addpin Wibowo (Politeknik Bisnis Indonesia, 2023)
This study aims to 1) describe the variables of product quality, price, repurchase intention and customer satisfaction of Samsung Smartphones 2) analyze the effect of product quality and price on customer satisfaction of Samsung Smartphones, 3) analyze the effect of product quality and price on customer repurchase intention of Samsung Smartphones, 4) analyzing customer satisfaction on repurchasing interest of Samsung Smartphone customers, 5) analyzing product quality and price on customer repurchasing interest through Samsung smartphone customer satisfaction. This research was conducted at Plaza Pondok Gede, Bekasi City using the glue show method with a sample of 100 respondents consisting of Samsung Experience Store customers. Methods of data analysis using descriptive quantitative method with path analysis. The results of this study indicate that: 1) the variables of product quality, price, customer satisfaction have contributed directly or indirectly to the increasing repurchase interest of Samsung Smartphone customers 2) there is a positive influence of product quality and price on customer satisfaction of Samsung Smartphones, 3) there is a positive influence of product quality and price on repurchase intention of Samsung Smartphone customers, 4) there is a positive effect of customer satisfaction on repurchasing intention of Samsung Smartphone customers, 5) there is a positive effect of product quality and price on repurchase intention through Samsung Smartphone customer satisfaction.